022 Evaluating diversion of alcohol related attendances: the EDARA study. Issue 12 (21st November 2019) - Goodacre, Steve; Irving, Andy; Young, Tracey; O'Cathain, Alicia; Buykx, Penny; Moore, Simon
Abstract : Background: Alcohol Intoxication Management Services (AIMS), commonly known as 'drunk tanks', provide an alternative to emergency department (ED) attendance for intoxicated adults at times of high incidence. The EDARA study evaluated the role of AIMS in the emergency care system and night time economy. Here we present findings describing AIMS activity and running costs, and estimating the effect of AIMS on ED attendance rates and ED user experience. We identified six cities with AIMS and collected data relating to attendances and costs of running the service. We matched these cities with six cities without AIMS and used routine NHS data to estimate the effect of AIMS operation upon ED attendances during hours of AIMS activity. We also surveyed ED user experience over matched time periods of AIMS activity in cities with and without AIMS. Mean attendance rates at the AIMS ranged from 2.7 to 11.8 per night. The mean running cost for an AIMS was £1635 per night (range £1075 to £2265) and the mean cost per attendance was £222.50 (range £132.27 to £583.8). Overall AIMS were associated with reduced ED attendances (−5.30 per night, p<0.05, 95% CI −9.62 to −0.62). However, the effect varied markedly between individual AIMS, ranging from 4.93 fewer attendances to 3.32 additional attendances per night. There was no significant effect from AIMS on ED user aggregate service rating score (coefficient 0.060, p=0.372), perception of feeling threatened (−0.037, p=132), aggregate negative experience score (−0.147, p=0.196), and overall service rating score (0.25, p=0.440). AIMS vary markedly in activity, running costs and effect on ED attendances, so estimating overall effects is probably inappropriate. The most active and expensive AIMS appeared to be associated with the greatest effect on ED attendances. We identified no effect on ED user experience.